Educational Information Communication: Self-Disclosure Ability and Job Stress - Yustiana Olfah; Isnaniah Isnaniah; Furaida Khasanah; Katri Andini Surijati; Titik Endarwati; Eko Suryani (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Work stress is an occupational health problem experienced by many health workers and service sector workers, with an impact on performance, job satisfaction, and mental health. Studies have shown that work stress is not only influenced by workload, but also by the quality of education, information and communication (EIC), as well as self-disclosure skills in the work environment. Communication, Information, and Education (KIE) in the context of health is an interactive message delivery process aimed at changing the understanding, attitudes, and health behaviours of the message recipients. Its main goal is to improve health literacy and healthy decision-making. This article aims to examine the relationship between EIC, self-disclosure ability, and work stress based on published research results.The method used is a literature review of relevant national and international articles. The literature was searched through health and human resource management journals, focusing on the variables of educational communication, self-openness, support from superiors and colleagues, and work stress levels.The results showed that 60–75% of articles reported that work stress was in the medium to high category, especially in workers with limited access to information and ineffective communication. About 55–70% of studies show that low self-disclosure skills are associated with increased work stress, interpersonal conflict, and emotional exhaustion. In contrast, more than 65% of studies reported that educational interventions, two-way communication, as well as employer support were associated with reduced work stress, with a decrease in stress scores ranging from 15–30% after communication or training interventions. A work environment that encourages openness and supportive communication is also associated with an increase in job satisfaction of up to 20–25%.In conclusion, effective education and communication, along with strengthening self-disclosure skills, play an important role in managing work stress. This approach has the potential to be a promotive and preventive strategy in occupational health programs, especially in the service and health sectors.